Would I Care if I Knew? Image Concerns and Social Confirmation in Giving - Alexander S. Kritikos; Jonathan H. W. Tan (Institute for the Study of Labor (IZA), 2014)
This paper experimentally investigates the nature of image concerns in gift giving. For this, we test variants of dictator and impunity games where the influences of social preferences on behavior are kept constant across all games. Givers maximize material payoffs by pretending to be fair when receivers do not know the actual surplus size, implying that portraying an outward appearance of norm compliance matters more than actual compliance. In impunity games, receivers can reject gifts with no payoff consequence to givers. In the face of receivers' feedback, some givers ensure positive feedback by donating more while some avoid negative feedback by not giving at all. Removing feedback reduces the incentive to give altogether. Differing behavior in the four games implies that social confirmation plays a crucial role in the transmission of image concerns in giving.
Keywords: C78; C92; 330; dictator game; impunity game; experiment; image; social confirmation